Hemoptysis and Unilateral Pulmonary Infiltrates due to Severe Acute Mitral Regurgitation from Papillary Muscle Rupture - Joanna Wieckowska; Nicholas Diloreto; Shannon Hood; Isabella Chojnacki; Dalia Zakri (Case Reports in Pulmonology)
Acute mitral regurgitation typically presents with dyspnea, chest pain, and hemodynamic instability. It is an uncommon cause of hemoptysis. We present a case of a patient presenting with dyspnea and hemoptysis without hemodynamic instability along with right-sided infiltrate on chest radiography a few days after an acute inferolateral STEMI who was found to have posterior papillary muscle rupture resulting in acute mitral regurgitation. Our case illustrates that the aforementioned symptoms and signs should raise concern for acute mitral regurgitation and prompt cardiac evaluation in the appropriate clinical setting as they may mimic acute pulmonary processes and delay critical diagnosis and treatment.